Code Switching and Code Mixing on “Ngobrol Sore Semaunya” Podcast - Agathar Narulia Sekar Langit; Isti'anatul Hikmah; Dita Surwanti (International Journal of English Learning and Applied Linguistics (IJELAL), 2022)
This study focused on finding the types and the reasons behind the use of code switching and code mixing on “Ngobrol Sore Semaunya” podcast. This study is aimed to answer these following questions (1) What are the types of code switching and code mixing found on "Ngobrol Sore Semaunya" podcast? (2) What are the reasons for the use of code switching and code mixing during the “Ngobrol Sore Semaunya” podcast? It is qualitative study through document analysis to analyze the data by describing findings. The source of data was from “Ngobrol Sore Semaunya” podcast episode 2 and 13. While, the data were taken from the utterances of the host and the guests that contain code switching and code mixing. The result showed that there are 177 utterances on “Ngobrol Sore Semaunya” podcast indicating code switching; 53 data are considered as intra-sentential, 4 data are classified as tag switching, and 120 data belong to inter-sentential. Furthermore, the researcher found 59 data of code mixing include 45 insertion and 14 alternations. In both data 1 and data 2, the speakers did not utter congruent lexicalization type of code mixing. The speakers in “Ngobrol Sore Semaunya” podcast used code switching include talking about a particular topic, quoting somebody else, being emphatic about something, interjection, and repetition used for clarification. However, the speakers did not do code switching to express group identity. Last, the reasons that generated the speakers to utter code mixing are the social roles and relationship of the participants, situational factors, message-intrinsic consideration, and language attitude including social dominance and security. To sum up, there were three types of code switching and two types of code mixing appeared on “Ngobrol Sore Semaunya” podcast with varied reasons that lead the host and the guests uttered the code switching and the code mixing